Modern domestic historiography of the repressive policy of the Soviet State regarding the peasantry of the Ukrainian SSR, 1921-1939: the regional aspect - Olha Dovbnia (Cхід, 2018)
The policy of the Bolsheviks in relation to the peasantry of the Krai is an actual direction of research of modern domestic repressology. In the article the current state of Ukrainian historiography reflection of the regional aspect of the Communist totalitarian regime’s repressive policy regarding the peasantry of the Ukrainian SSR in 1921-1939 years is analyzed. It is established that the researchers paid the greatest attention to clarification of the causes, forms, consequences of the use of punitive measures of the Communist-Soviet power against peasants of the South Ukraine, Dnieper, Podolia, South-Eastern Volhynia, Donbas, North-Eastern region of Ukraine, Kirovohrad, Kyiv regions during the grain procurement crisis of 1927/1928, 1928/1929, the forced continuous collectivization and the Holodomor of 1932-1933. Moreover, due to research it is established, that the implementation of the «kulak operation» of 1937-1938 years in the majority of regions are unexplored. Research of modern Ukrainian historians, who specialize in this issue, shows that the political repression against the peasantry of the Ukrainian SSR in 1921-1939 focused on solving economic problems, suppressing all forms of resistance, and modeling social processes and regional peculiarities of repressive politics depended on combinations of the directives of the center, initiatives of the local authorities and the public security authorities. The repression was not limited to a specific group of the richest peasantry but was directed against the peasantry opposing a forced collectivization. The author of the article is the author of the letter of appreciation of the specifics of the implementation of the Operative Punishment of the People's Commissar of Internal Affairs of the Social Security Service of the USSR, M. Єzhova, No. 00447, "On the operation of reprimanding the number of kurkulists, carnies of evil and the anti-Radar elements" dated 30 June 1937.